Hubungan Gerakan Sujud Terhadap Fleksibilitas Otot Para Vertebra - Najiib, Muhammad Mirda Marits; , Isnaini Herawati, SSt. FT, M. Sc (2016)
Background: Every human being will experience a period of decline in the quality of organs. And spine (vertebra) is one of the important part that has a major role to other organs. Thus the need for maintenance of body condition early by strengthening or stretching exercises such as that used motion prostration. Where prostration is obligatory worship in harmony in our daily. Objective: To determine the relationship of movement prostration to the flexibility of the spine muscles. Methods: This type of research is observational using cross sectional method with a sample of 28 people. Measuring instrument used is the Med-Line. Data were analyzed using Kendall's Tau-b test to test the relationship. Results: There was a relationship prostration to the flexibility of muscle movement of the vertebrae with a p-value of 0.616 that prostration as much as 1466 times the frequency has additional flexibility 4cm. Conclusion: The application of prostration motion for a month with more and more frequency, the higher the flexibility of the muscles of the spine. Keywords: prostration motion, muscle flexibility of the vertebrae.